Dampak Bimbingan Pranikah Bagi Pasangan Suami Istri Terhadap Keharmonisan Rumah Tangga di Kecamatan Pahandut - Ahmad Faisal (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Pre-marital classes that have been running at KUA for a long time have now been replaced with pre-marital guidance since 2019. This is based on the idea of ​​the coordinating ministry for human development and culture, pre-marital guidance is still carried out under KUA coordination in each respective region, guidance Pre-wedding is carried out after the prospective bride and groom register at the KUA. In this study the researchers formulated 2 problem formulations, namely the first how is the practice of premarital guidance for prospective brides that has occurred in the Pahandut sub-district? And second what is the impact of premarital counseling on household harmony in the Pahandut sub-district? This research is located in Central Kalimantan focusing on the Pahandut sub-district, and what will be examined is the KUA pre-marital organizers.